Deciphering the Taxonomic Delimitation of Ottelia acuminata (Hydrocharitaceae) Using Complete Plastomes as Super-Barcodes - Ji, Yunheng; Yang, Jin; Landis, Jacob B.; Wang, Shuying; Yang, Zhenyan; Zhang, Yonghong (Frontiers in Plant Science, 2021)
Accurate species delimitation and identification, which is a challenging task in traditional morphology-based taxonomy, is crucial to species conservation. Ottelia acuminata (Hydrocharitaceae) is a severely threatened submerged macrophyte endemic to southwestern China. The taxonomy of O. acuminata, which has long been in dispute, remains unresolved, impeding effective conservation and management practices. Here, we aim to address the long-standing issues concerning species boundary and intraspecific subdivision of O. acuminata using complete plastome sequences as super-barcodes. The taxonomic delimitation of O. acuminata was explored using phylogenetic inference and two independent sequence-based species delimitation schemes: automatic barcode gap discovery (ABGD) and multi-rate Poisson tree processes (mPTP). The reciprocally reinforcing results support the reduction of the closely related congeneric species, O. balansae and O. guanyangensis, as two conspecific varieties of O. acuminata. Within the newly defined O. acuminata, accurate varietal identification can be achieved using plastome super-barcodes. These findings will help inform future decisions regarding conservation, management and restoration of O. acuminata. This case study suggests that the use of plastome super-barcodes can provide a solution for species delimitation and identification in taxonomically difficult plant taxa, thus providing great potential to lessen the challenges of inventorying biodiversity, as well as biologically monitoring and assessing threatened species.